Examining the Geoeconomic Implications of China’s Belt and Road Initiative for US Preeminence in the Horn of Africa - Tewodros Woldearegay; Maru Mathewos Erbeto; Dereje Fikre Jima; Solomon Nigussie Worku (China Quarterly of International Strategic Studies)
Focusing on the US–China rivalry in the Horn of Africa (HoA), this study investigates the geoeconomic implications of China’s Belt and Road Initiative (BRI) on long-standing US preeminence, using offensive realism as a theoretical lens. Based on an in-depth literature review and using a qualitative research approach, the authors examine Beijing’s growing geoeconomic engagement with the HoA and its consequences for great power competition on the African continent. It examines the strengths and weaknesses of President Biden’s Build Back Better World (B3W), a development initiative designed to counter China’s BRI economic influence on the HoA. The study concludes that both the BRI and B3W initiatives and their implementation strategies demonstrate that both Beijing and Washington have strong national interests in the HoA regions, resulting in fierce geopolitical competition.